2019
DOI: 10.3390/polym11081365
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Behavior of Wood Plastic Composites by Addition of Graphene Nanoplatelets

Abstract: Wood plastic composites (WPCs) incorporating graphene nano-platelets (GNPs) were fabricated using hot-pressed technology to enhance thermal and mechanical behavior. The influences of thermal filler content and temperature on the thermal performance of the modified WPCs were investigated. The results showed that the thermal conductivity of the composites increased significantly with the increase of GNPs fillers, but decreased with the increase of temperature. Moreover, thermogravimetric analysis demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Referring to Rajan et al [59], samples with 15 wt.% graphene increased the thermal conductivity by 135%, although, as emphasised by the authors, the absolute values were still well below 1 W/mK, which is not sufficient for many applications. Analogous results were obtained by Zhang et al [60], who manufactured composite samples from polyethylene, graphene nanoplatelets (0, 3, 6, 9, or 12 wt.%), and poplar wood fibres (40 wt.%), with maleic anhydride-grafted polyethylene (MAPE) as a compatibility agent (3 wt.%). The components were dried, mixed, and extruded using a co-rotating twin-screw extruder.…”
Section: Electrical and Thermal Conductivitysupporting
confidence: 76%
See 2 more Smart Citations
“…Referring to Rajan et al [59], samples with 15 wt.% graphene increased the thermal conductivity by 135%, although, as emphasised by the authors, the absolute values were still well below 1 W/mK, which is not sufficient for many applications. Analogous results were obtained by Zhang et al [60], who manufactured composite samples from polyethylene, graphene nanoplatelets (0, 3, 6, 9, or 12 wt.%), and poplar wood fibres (40 wt.%), with maleic anhydride-grafted polyethylene (MAPE) as a compatibility agent (3 wt.%). The components were dried, mixed, and extruded using a co-rotating twin-screw extruder.…”
Section: Electrical and Thermal Conductivitysupporting
confidence: 76%
“…The existing literature indicates that enriching WPCs and NFPCs with carbon nanomaterials may be highly beneficial to the performance of the WPCs/NFPCs. Expanding on this, in general, it has been shown that the addition of graphene or carbon nanotubes may result in an improvement of mechanical properties [53][54][55][56], an increase in electrical and thermal conductivity [57][58][59][60], a decrease in water absorption, and an improvement of thermal stability [61,62] and/or fire retardancy [60]. All of these tested properties are listed in Table 1.…”
Section: Improvement Of Wpc/nfpc Performance By the Addition Of Carbo...mentioning
confidence: 94%
See 1 more Smart Citation
“…Modification with graphene and graphene derivatives has been realized recently as a way to increase the mechanical properties of polymers as well as wood polymer composites and/or to impart functionality, such as thermal/electrical conductivity or electromagnetic shielding interference [1][2][3]. The application of graphene nanoplatelet (GNPs) in composites is foreseen to grow between 2018 and 2025 by about 40% as it is being increasingly researched for composite-utilizing industries, such as construction, aerospace, and automotive sectors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The field combines wood processing techniques for fiber or filler preparation with polymer science and engineering, and a range of polymer processing techniques including extrusion, injection molding, compression molding, and pultrusion. Wood plastic composites (WPCs) incorporating graphene nano-platelets (GNPs) were fabricated using hot-pressed technology to enhance thermal and mechanical behavior [32]. The influences of thermal filler content and temperature on the thermal performance of the modified WPCs were investigated.…”
mentioning
confidence: 99%